Achieving Superior Ductility at High Strain Rate in a 1.5 GPa Ultrahigh-Strength Steel without Obvious Transformation-Induced Plasticity Effect - Yao Lu; Tianxing Ma; Zhiyuan Liang; Li Liu (Metals, 2024)
The development of ultrahigh-strength steels with good ductility is crucial for improving the crashworthiness of automobiles. In the present work, the mechanical responses and deformation behaviors of 1.5 GPa ultrahigh-strength steel were systematically investigated over a wide range of strain rates, from 10−3 s−1 to 103 s−1. The yield strength and tensile elongation at quasi-static strain rate (10−3 s−1) were 1548 MPa and 20%, respectively. The yield strength increased to 1930 MPa at an extremely high strain rate (103 s−1), and the steel maintained excellent ductility, with values as high as 17%. It was found that the prevailing of the transformation-induced plasticity (TRIP) effect at quasi-static condition resulted in the formation of fresh martensite. This produced strong hetero-deformation-induced (HDI) stress and strain partitioning, contributing to the enhancement of strain hardening. The TRIP effect is remarkably suppressed under high strain rates, and thus the retained austenite with excellent deformation ability sustains the subsequent deformation, leading to superior ductility when the TRIP effect and HDI strengthening are retarded. Ultrahigh-strength steel with great strength–ductility combination over a wide range of strain rates has great potential in improving component performance while reducing vehicle weight.